"Lupara Bianca" a way to hide cadavers after Mafia homicides. A cemetery of Italian Mafia. A case study. Issue 3 (May 2015) - Pomara, Cristoforo; Gianpaolo, Di Peri; Monica, Salerno; Maglietta, Francesca; Sessa, Francesco; Guglielmi, Giuseppe; Turillazzi, Emanuela
Highlights Mafia murders are always finalized to establish one's potency or capacity to control the territory of action of their criminal activities. The "Lupara Bianca" seems to be a method primarily used in Mafia homicides with the main purpose to hide cadavers and attempting to throw the inquiry off the track for the longer time. A complete forensic investigation in these cases should include both radiological investigations and DNA profiling.